PERAN MELANOSIT PADA PROSES UBAN - Sinaga, Roslin; Wangko, Sunny; Kaseke, Marie (JURNAL BIOMEDIK : JBM, 2012)
Abstract: Hair is a long keratinous structure derived from invaginated epidermal epithelial cells. Hair varies in colour, diameter, and distribution, depending on race, age, gender, and regions of the body. Histologically, the structure of hair is formed by three strata, or inter alia: medulla, cortex, and cuticle. Melanocytes of hair follicles are specific cells that play some important roles in the production of hair pigment (melanin). Gray hair appears due to aging. In this case melanocyte activities in melanin production decrease gradually. There are other external factors that can influence the appearance of gray hair e.g smoking and hair dyes; both of them produce hydrogen peroxyde which inflict eumelanogenesis. Eumelanin is the dark-brown melanin, meanwhile feomelanin is the yellow one. An internal factor related to the early appearance of grey hair is a genetically induced one. Keywords: grey hair, melanocyte, hair.   Abstrak: Rambut merupakan struktur panjang berkeratin yang berasal dari invaginasi epitel epidermis. Warna, ukuran dan  penyebaran rambut bervariasi sesuai ras, umur, jenis kelamin, dan area tubuh. Rambut terdiri atas tiga lapis sepusat yaitu: medula, korteks, dan kutikula. Melanosit folikel rambut merupakan sel-sel khusus yang secara langsung mengendalikan produksi pigmen rambut, yaitu melanin. Munculnya rambut uban diakibatkan proses penuaan dimana aktivitas sel melanosit juga ikut menurun secara bertahap. Beberapa faktor eksternal yang dapat memicu rambut menjadi uban antara lain  merokok atau penggunaan cat rambut, yang merangsang pembentukan hidrogen peroksida sehingga sintesis eumelanin menjadi terganggu. Eumelanin ialah jenis melanin yang berwarna coklat-hitam, sedangkan feomelanin berwarna pirang. Faktor internal lain yang berkaitan dengan tumbuhnya uban lebih awal ialah genetik. Kata kunci: uban, melanosit, rambut.